2011
DOI: 10.1177/1479164111420890
|View full text |Cite
|
Sign up to set email alerts
|

Variability of clopidogrel response in patients with type 2 diabetes mellitus

Abstract: The global prevalence of diabetes mellitus (DM) continues to climb, with a commensurate increase in the cardiovascular complications associated with DM and representing a global public health crisis.Macrovascular atherosclerotic disease, most often manifesting as coronary heart disease (CHD) and its complications, account for the majority of morbidity and mortality associated with DM, underscoring the imperative to develop more effective and specific strategies towards mitigation of the cardiovascular disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 69 publications
(108 reference statements)
0
20
0
2
Order By: Relevance
“…Previous large scale trials, such as the Japanese Primary Prevention of Atherosclerosis with Aspirin for Diabetes (JPAD) trial [34], and the Prevention of Progression of Arterial Disease and Diabetes (POPAPAD) trial [35], have shown low efficacy of aspirin monotherapy for prevention of cardiovascular events in patients with diabetes. In addition, recent data show that responses to clopidogrel in patients with diabetes are suboptimal [36]. Such data suggest that diabetes is associated with considerable resistance to aspirin and clopidogrel therapy, and such insufficient antiplatelet responses could be an underlying causal factor for the frequent END observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous large scale trials, such as the Japanese Primary Prevention of Atherosclerosis with Aspirin for Diabetes (JPAD) trial [34], and the Prevention of Progression of Arterial Disease and Diabetes (POPAPAD) trial [35], have shown low efficacy of aspirin monotherapy for prevention of cardiovascular events in patients with diabetes. In addition, recent data show that responses to clopidogrel in patients with diabetes are suboptimal [36]. Such data suggest that diabetes is associated with considerable resistance to aspirin and clopidogrel therapy, and such insufficient antiplatelet responses could be an underlying causal factor for the frequent END observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[97][98][99] Another potential option for reducing CV events in patients with diabetes is the P2Y 12 inhibitor clopidogrel (Plavix; Sanofi-Aventis, Bridgewater, NJ, USA). However, a lack of antiplatelet effects similar to that observed with aspirin has been observed in patients with diabetes [100] and, in patients at high risk of a CV event (i.e. evidence of a previous occlusive event or other predisposing condition), clopidogrel alone provided no additional CV protection compared with aspirin.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 91%
“…[32] Because clopidogrel and aspirin exert their antiplatelet effects through two separate pathways (i.e. reduced TXA 2 production via COX inhibition with aspirin [10] and ADP-induced activation of GPIIb-GPIIIa with clopidogrel [100][101][102][103]), it was hypothesized that combination therapy with both of these antiplatelet agents might provide additional protection against CVD. In patients with type 2 diabetes, combination therapy with aspirin 81 mg/day and clopidogrel 75 mg/day for 1 month significantly reduced ADP-, epinephrine-and collagen-stimulated platelet aggregation compared with aspirin 81 mg/day alone; however, no significant difference in arachidonic acid-induced aggregation was observed between treatment groups.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…[79] Although Clopidogrel resistance has been studied more extensively than aspirin resistance, its prevalence estimates in patients with diabetes also varies based on assay, patient population and dose of Clopidogrel. [80] However, inter-individual variability in platelet response to Clopidogrel is now a well-established concept. Clopidogrel hypo-responsiveness is more prevalent in patients with diabetes, and is highest in insulin-treated patients.…”
Section: Clopidogrel Resistance In Diabetesmentioning
confidence: 99%